Negotiating the Streets Hidden Resilience among Grown-Up Street Children in Manila. [article]. - Wartenweiler, D.
This study investigated processes of hidden resilience of grown-up street dwelling children who still live on the streets in an inner city of Manila. Two adult street dwellers were purposively sampled based on their resilient functioning across four domains. A naturalistic narrative design was employed and the collected narratives were thematically analyzed. Results showed that both participants had experienced non-normative adversity, such as severe poverty, death of a parent and of other significant persons, dropping out of school, and exposure to drugs and vice. Six interacting resilience processes led to adaptive outcomes: having a significant adult, early involvement in work, distancing self from peers, delinquency as turning point, early parenthood, and spirituality. The identified processes and their corresponding outcomes reflect an idiosyncratic and context-specific adaptation to adversity, hence providing evidence for hidden resilience among grown-up street dwelling children as an atypical, discursive negotiation between individual and environment. The narratives illustrate the lack of basic rights and the great fragility in the participants? lives, but also enormous perseverance, contentment, meanings made, and generativity. The participants are not depicted as victims or delinquents, but their voices speak of agency, hope, and dignity.